Advanced glycation end-products are associated with diabetic neuropathy in young adults with type 1 diabetes - Al-Saoudi, Elaf; Christensen, Marie M. B.; Nawroth, Peter Paul; Fleming, Thomas; Hommel, Eva E.; Jørgensen, Marit E.; Fleischer, Jesper; Hansen, Christian S. (Frontiers in endocrinology, 2022)
Aims/hypothesisAdvanced glycation end-products (AGEs) may contribute to the development of diabetic neuropathy. In young adults with type 1 diabetes, we aimed to investigate the association between AGEs and cardiovascular autonomic neuropathy (CAN) and distal symmetric polyneuropathy (DSPN).MethodsThis cross-sectional study comprised 151 young adults. CAN was assessed by cardiovascular autonomic reflex tests; lying-to-standing test, deep breathing test (E/I), Valsalva manoeuvre, and heart rate variability indices; and the mean square of the sum of the squares of differences between consecutive R-R intervals and standard deviation of normal-to-normal intervals (SDNN), high- (HF) and low-frequency (LF) power, total frequency power, and the LF/HF ratio. DSPN was assessed by light touch, pain and vibration perception threshold (VPT), neuropathy questionnaires, and objective measures. AGEs were analysed in four groups using z-scores adjusted for relevant confounders and multiple testing: i) “glycolytic dysfunction”, ii) “lipid peroxidation”, iii) “oxidative stress”, and iv) “glucotoxicity”.ResultsA higher z-score of “glycolytic dysfunction” was associated with higher VPT (4.14% (95% CI 1.31; 7.04), p = 0.004) and E/I (0.03% (95% CI 0.01; 0.05), p = 0.005), “lipid peroxidation” was associated with higher LF/HF ratio (37.72% (95% CI 1.12; 87.57), p = 0.044), and “glucotoxicity” was associated with lower SDNN (−4.20% (95% CI −8.1416; −0.0896), p = 0.047). No significance remained after adjustment for multiple testing.Conclusions/interpretationsIn young adults with type 1 diabetes, increased levels of AGEs involving different metabolic pathways were associated with several measures of CAN and DSPN, suggesting that AGEs may play a diverse role in the pathogeneses of diabetic neuropathy.